Study of Methods For Enhancing Quality of Learning and Performance In Higher Education: Improving Learning and Performance in Higher Education: A Paradigm Shift in Study Methods (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Education is  an investment to  development and  poor  study  methods  should  not compromise  the  mandate of  higher  education  institutions to  generate,  preserve and disseminate knowledge and produce high quality graduates. Universities admit studentswith varying backgrounds in terms of learning/study styles, levels of preparedness andconcepts  of university education. Some were "drilled", spoon fed, taught for exams, orhave wrong purposes/values of university learning. These negatively impact on theirstudy  skills  and  achievement.  In  complementing  the  role played  by academic  staff,students need to be conscious of their personality and study ethics as they influence studying. It is futile to teach well while students lack the fundamentals to conceptualize and internalize  the  new knowledge.  This paper  proposes a paradigm  shift  in studymethods and suggests strategies for both the lecturers and the students in universities towards  improved  learning and  performance. The paper is  based  on  the "distributedlearning approach" to adequately cater for individual differences that exist among thestudents. The model is significant for university students, most of whom begin seriousstudying  on realization  that  examinations are around  the  corner.  This  causes stress,confusion and tendency to cheat in examinations. Distributed learning model will address the study space needs and theefficiency and effectiveness of study methods